Data-Level Parallel Approaches for the H.264/AVC: A Review from the Encoder and the Decoder Perspectives (International Journal of Engineering and Computer Science, 2017)
In order to enable easier transmission and storage of videos, video-coding techniques are used as data compression process that is intended to reduce the size of raw video without sacrificing its visual quality. The H.264 is relatively one of the recent video compression standards, which has proved to outperform former standards in terms of compression efficiency. However, it’s associated with mush higher computational complexity. Several software-based as well as hardware-based approaches have been suggested to tackle this problem by using several flavours of data-level parallel approaches for the encoder and decoder sides. In this paper, these approaches are presented and compared in form of a comparative review. The suitability of one particular approach is determined based to the architecture used.